The role of consciousness in the phonological loop: hidden in plain sight - Buchsbaum, Bradley R. (Frontiers in Psychology, 2013)
We know from everyday experience that when we need to keep a small amount of verbal information “in mind” for a short period, an effective cognitive strategy is to silently rehearse the words. This basic cognitive strategy has been elegantly codified in Baddeley and colleagues model of verbal working memory, the phonological loop. Here we explore how the intuitive appeal of the phonological loop is grounded in the phenomenological experience of subvocal rehearsal as consisting of an interaction between an “inner voice” and an “inner ear”. We focus particularly on how our intuitions about the phenomenological experience of “inner speech” might constrain or otherwise inform the functional architecture of information processing models of verbal working memory such as the phonological loop; and how, indeed, how ideas about consciousness may offer alternative explanations for the dual nature of inner speech in verbal working memory.